Isolation and characterisation of a monocyte protein C receptor : implications for novel therapeutic strategies in sepsis - Galligan, Leeona (Trinity College (Dublin, Ireland). School of Medicine. Discipline of Haematology, 2003)
The protein C (PC) pathway provides a unique interface between the processes of coagulation, inflammation and fibrinolysis. Used as an adjunct to standard treatment, PC/activated PC to date, has been shown to be the only effective therapeutic intervention to reduce morbidity and mortality levels associated with severe sepsis/septic shock. Although its exact mechanism of action remains to be established, PC binding to the recently described endothelial protein C receptor (EPCR) appears to be a key feature. Given the significance of monocytes in the pathophysiology of severe sepsis, the possible expression of a protein C receptor on the monocyte membrane was investigated.
Keywords: Haematology, Ph.D.; Ph.D. Trinity College Dublin